IMPLEMENTATION OF THE GREEN FLIGHT INTO AIRSPACE OF UKRAINE - Bogunenko, Nikolay; Semydko, Yulia (Proceedings of National Aviation University (archive), 2014)
The article deals with the analysis of the current Green Flight challenge in Ukraine, investigation of thefactors that influence on Green Flights implementation, analysis of all systems that are corresponded to conception ofGreen Flights development, current problems and ways of their solution.